2015
DOI: 10.1590/0104-0707201500004040014
|View full text |Cite
|
Sign up to set email alerts
|

Use of Clinical Indicators in the Evaluation of Prevention and Control Practices for Bloodstream Infection

Abstract: ABSTRACT:The aim of this study was to evaluate the compliance of the implemented prevention and control practices for central venous catheter-related bloodstream infection, through clinical indicators. An observational study, with a quantitative approach, was conducted. The case series was based on 2064 evaluations, conducted through direct observation and medical records, using a manual for evaluating the quality of cross-infection control practices. The results showed that the indicator for the registrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
10

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
0
10
0
10
Order By: Relevance
“…Therefore, adherence to hand hygiene practice favors the reduction of adverse events 17 . Studies 17 , 23 - 24 have shown that, although widely disseminated, hand hygiene practices are not yet within the expected standards. Nursing professionals do recognize the importance of this action, but do not incorporate it into their care practices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adherence to hand hygiene practice favors the reduction of adverse events 17 . Studies 17 , 23 - 24 have shown that, although widely disseminated, hand hygiene practices are not yet within the expected standards. Nursing professionals do recognize the importance of this action, but do not incorporate it into their care practices.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, among procedures that applied the checklist of verification for CVC insertion, there was a high adherence rate in the follow-up of the 11 recommended components or measures, with overall adherence higher than 80%. However, studies on adherence assessment, related to CVC insertion, show the difficulty in achieving general adherence greater than or equal to 80% (16,(18)(19)(20) . In this regard, one must remember that the performance of procedures involving aseptic techniques and safe practices contribute to the reduction of adverse events; however, to ensure such safe and risk-free care, the management must focus on strategies that favor better adherence through constant monitoring and continuing education.…”
Section: Resultsmentioning
confidence: 99%
“…The use of clinical indicators of quality in CVC care protocols favors the identification not only of indices concerning compliance and performance of such care, but also the identification of concrete situations interfering in the results, enabling direct and specific interventions to improve them. 30,33 Even though clinical indicators of performance related to CVCs were not the object of analysis in this study, they should be considered an important tool to assess and support the use of care bundles to prevent CVC-BSI.…”
Section: Discussionmentioning
confidence: 99%